Effect of water stress on some growth parameter in tow pistachio seedlings rootstock (Journal of Hama University, 2022)
This experiment was carried out during the 2019 and 2020 seasons in the Pistachio Office on two-year-old seedlings, they were planted in bags of polyethylene of dimensions (35 * 45) to study the effect of water stress (well irrigation, moderate water stress, severe water stress) on growth of two pistachio rootstocks (P.vera) and (P.atlantica), and were applied irrigation treatments from the beginning of May until end of July, then we have studied some growth parameters such as height , leaf area, chlorophyll and proline concentration, The results showed decrease in most of growth parameters with increasing water stress, and it has been observed a signifecant superiority of the (P.atlantica) in its ability to tolerate water stress, plant height reached the highest value under well irrigation treatment in both rootstocks respectively (P.vera and P.atlantica) (92.4, 77.4) cm, while it decreased to reach lowest value when treating severe stress (55.5, 58.8) cm, leaf area was also significantly decreased under severe water stress treatment in both rootstocks respectively (123.76 and 169.92) cm2.Total chlorophyll concentration decreased to its lowest value under severe water stress treatment in (P.vera) (36.19 mg/g wet weight), while it was ( 42.96 mg/g wet weight) in (P.atlantica) seedlings.Proline content increased and reached to maximum value under sever water stress respectively (50, 56.14)mg/g wet weight, which indicates the ability of (P.atlantica) to tolerate water stress and its adaptation to severe water shortage in the soil compared to (P.vera).